2004
DOI: 10.1073/pnas.0308264100
|View full text |Cite
|
Sign up to set email alerts
|

Transition state stabilization by general acid catalysis, water expulsion, and enzyme reorganization in Medicago savita chalcone isomerase

Abstract: In aqueous solution, Medicago savita chalcone isomerase (CHI) enhances the reaction rate for the unimolecular rearrangement of chalcone (CHN) into flavanone by seven orders of magnitude. Conformations of CHN and their relative free energies in water and CHI were investigated by the thermodynamic perturbation method. In water, CHN adopts two conformations (I and II) with conformation I being higher in energy than conformation II by 3 kcal͞mol. Only I can give rise to a near attack conformer (NAC) where the nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 19 publications
0
36
1
2
Order By: Relevance
“…Subsequently, malonyl-CoA is added to p-coumaroyl-CoA and yields tetrahydroxychalcone by the enzyme chalcone synthase. Finally, chalcone isomerase converts the C15 compound tetrahydroxychalcone into (2S)-flavanones (85)(86)(87). These flavonoids, including a diverse family of polyphenols, have been proven with health-promoting effects especially in preventing various human pathological risks (88,89).…”
Section: Metabolism Of Small Molecules Related To Detoxification and mentioning
confidence: 99%
“…Subsequently, malonyl-CoA is added to p-coumaroyl-CoA and yields tetrahydroxychalcone by the enzyme chalcone synthase. Finally, chalcone isomerase converts the C15 compound tetrahydroxychalcone into (2S)-flavanones (85)(86)(87). These flavonoids, including a diverse family of polyphenols, have been proven with health-promoting effects especially in preventing various human pathological risks (88,89).…”
Section: Metabolism Of Small Molecules Related To Detoxification and mentioning
confidence: 99%
“…In contrast, the type II CHIs appear to be legume specific and possess additional catalytic activity, which allows them to convert 4, 2#, 4#-trihydroxychalcone (isoliquiritigenin) into (2S)-7, 4#-dihydroxyflavanone (liquiritigenin). A type II CHI isolated from alfalfa (Medicago sativa) has been extensively studied structurally and mechanistically (Jez et al, 2000Hur et al, 2004). These structure-function analyses suggest that the formation of a hydrogen bond network between the active site of CHI and its substrates is crucial for the enzyme's catalytic activity Hur et al, 2004).…”
mentioning
confidence: 99%
“…A type II CHI isolated from alfalfa (Medicago sativa) has been extensively studied structurally and mechanistically (Jez et al, 2000Hur et al, 2004). These structure-function analyses suggest that the formation of a hydrogen bond network between the active site of CHI and its substrates is crucial for the enzyme's catalytic activity Hur et al, 2004). Naringenin and liquiritigenin are the precursors of many flavonoid and isoflavonoid compounds.…”
mentioning
confidence: 99%
“…The deduced amino acid sequence of AmCHI1 displayed a 56% identity to that of MsCHI, a type-II CHI, which has been subjected to intense structural and mechanistic studies (Hur and Bruice 2003;Hur et al 2004;Jez et al 2000;Ruiz-Pernia et al 2008). Those studies revealed the importance of hydrogen bonds in the active site of MsCHI for catalysis, which involved Thr48, Tyr106, Asn113 and Thr190 as key residues (Figure 7).…”
Section: Amcifp1/amchi1mentioning
confidence: 99%